2020
DOI: 10.1002/adma.201908505
|View full text |Cite
|
Sign up to set email alerts
|

On the Controlled Loading of Single Platinum Atoms as a Co‐Catalyst on TiO2 Anatase for Optimized Photocatalytic H2 Generation

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201908505.Single-atom (SA) catalysis is a novel frontline in the catalysis field due to the often drastically enhanced specific activity and selectivity of many catalytic reactions. Here, an atomic-scale defect engineering approach to form and control traps for platinum SA sites as co-catalyst for photocatalytic H 2 generation is described. Thin sputtered TiO 2 layers are used as a model photoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
188
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(201 citation statements)
references
References 61 publications
11
188
2
Order By: Relevance
“…By means of an atomic-level defect engineering technique, Schmuki and coworkers used single Pt atoms to decorate the TiO 2 thin layer, which were highly active and stable for H 2 evolution under photocatalysis. [117] It was revealed that the H 2 evolution rate on atomic Pt sites was enhanced, which was 150 times higher than that on Pt NPs. In addition, atomic Pt Figure 7.…”
Section: Single Precious Metal Atoms Anchored On Inorganic Semiconducmentioning
confidence: 97%
See 1 more Smart Citation
“…By means of an atomic-level defect engineering technique, Schmuki and coworkers used single Pt atoms to decorate the TiO 2 thin layer, which were highly active and stable for H 2 evolution under photocatalysis. [117] It was revealed that the H 2 evolution rate on atomic Pt sites was enhanced, which was 150 times higher than that on Pt NPs. In addition, atomic Pt Figure 7.…”
Section: Single Precious Metal Atoms Anchored On Inorganic Semiconducmentioning
confidence: 97%
“…[116] Similarly, another single-atom system has been established for photocatalytic hydrogen evolution, in which atomically dispersed Pt was embedded into the oxygen vacancies of TiO 2 . [98,117] In carbon-based SACs, C vacancies can offer abundant defect sites to anchor various metal atoms via strong interactions. [34] Wei et al reported that isolated Pt atoms can be stably anchored on the C vacancies/edges of mesoporous carbon, which can effectively avoid aggregation of Pt atoms (Figure 5b).…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Over the past decade, self-aligned TiO 2 nanotubes (TNTs) grown on titanium have been extensively developed in environmental protection, photocatalysis [ [6] , [7] , [8] ], sensors [ 9 , 10 ], dye-sensitized solar cells [ 11 , 12 ], and biomedical applications [ [13] , [14] , [15] ] owing to their superior high-specific surface area, specific ion intercalation properties, photocatalysis property, and cost-effective synthesis. In particular, the terrific biocompatibility, corrosion resistance and size controllable properties of TNTs make them promising for biomedical applications, such as orthopedic/dental implants [ 16 , 17 ], blood contact materials [ 18 ], anti-microbial application [ 19 , 20 ], and drug delivery [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are major coloring agents used in industries for precious stones, paper, leather, plastic, textile, and food production. Hazardous waste water from dyeing process act as a major contaminant to the environment (Murugan and Parimelazhagan, 2014;Hejazi et al, 2020). The dye effluents are usually non-biodegradable, highly oxidizing, and stable to heat and light (Khataee and Mirzajani, 2010; which attributed to their toxicity, undesirable aesthetic, and carcinogenicity (Khalik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%